The Neuronal Glutamate Transporter EAAT3 in Obsessive-Compulsive Disorder - Escobar, Angélica P.; Wendland, Jens R.; Chávez, Andrés E.; Moya, Pablo R. (Frontiers in Pharmacology, 2019)
Obsessive compulsive disorder (OCD) is a heterogeneous psychiatric disorder affecting 1-3% of the population worldwide. About half of OCD afflicted individuals do not respond to currently available pharmacotherapy, which is mainly based on serotonin reuptake inhibition. Therefore, there is a critical need to search novel and improved therapeutic targets to treat this devastating disorder. In recent years, accumulating evidence has supported the glutamatergic hypothesis of OCD, and particularly pointing a potential role for the neuronal glutamate transporter EAAT3. This mini-review summarizes recent findings regarding the neurobiological basis of OCD, with an emphasis on the glutamatergic neurotransmission and EAAT3 as a key player in OCD etiology.